Evidence for a physiological role of hypothalamic gastrin-releasing peptide to suppress growth hormone and prolactin release in the rat. - Kentroti, S (1988)
Gastrin-releasing peptide (GRP) is localized to hypothalamic neurons and is a potent inhibitor of basal and growth hormone (GH)-releasing factor-induced GH secretion in the rat. It also acts similarly to inhibit opiate- and stress-induced prolactin (PRL) release. To determine the physiological significance of the peptide in the control of the release of these two hormones, a highly specific antiserum against GRP was injected into the third brain ventricle to immunoneutralize hypothalamic GRP. The injection of the antiserum initially did not alter levels of the hormones; however, both PRL and GH levels in the plasma began to increase within 3 and 3.5 hr, respectively. They were still significantly elevated 24 hr after the injection. There was no change in the plasma levels of either hormone in animals injected intraventricularly with a similar volume of normal rabbit serum (NRS). Mean plasma GH levels 24 hr after antiserum injection were more than twice those of the NRS-injected controls, whereas the PRL concentrations were 14-fold higher in the antiserum injected as compared to the control NRS-injected animals. A second similar injection of antiserum 24 hr after the first administration resulted in a slight and transient further increase in both GH and PRL levels so that they were both significantly (P less than 0.001) higher than those of the animals given a second injection of NRS. The anti-GRP antiserum was highly specific for GRP by radioimmunoassay procedures and this antiserum produced positive immunostaining of GRP neuronal perikarya and terminals within discrete hypothalamic nuclei. Beaded fibers and terminals were observed in the suprachiasmatic nucleus (SCN) and the area lateral and dorsal to the SCN in the region of the periventricular nucleus (PeVN). GRP-positive perikarya were observed in the parvocellular neurons of the paraventricular nucleus. In addition, GRP-positive cell bodies were observed in the PeVN in close proximity to the third ventricle. Furthermore, the median eminence displayed no immunostaining for GRP, and all traces of positive staining were abolished by preabsorption of the antiserum with GRP-27 (30 micrograms/ml), confirming the specificity of the antiserum. The combined results with immunoneutralization of GRP and the immunostaining of GRP neuronal elements in the hypothalamus support the physiological role of this peptide in the inhibitory control of both GH and PRL release.